Baptist movement in England in the late seventeenth century as reflected in the work and thought of Benjamin Keach, 1640-1704 - Spears, William Eugene (The University of Edinburgh, 1953)
Religious developments in the latter part of the Seventeenth Century form a neglected phase of English history. This may be due in part to the feeling that the people of this period were not greatly concerned with religion. In 1947 G.M. Trevelyan held that "after 1660, the reaction against Puritanism took the form not of Anglican devotionalism, but of indifference to religion." In 1950 G.R. Cragg maintained that the general works on the religious developments from 1660 to 1700 were old and that very few could claim to be satisfactory. Cragg wrote concerning the changes in thought within the Anglican Movement, whereas this is a study of the developments in the Baptist Movement as reflected in the work and thought of Benjamin Keach. The first section of this introduction gives a statement of the purpose of this study, the method of procedure used in the acquisition and presentation of the material, and the scope of this dissertation. It is the purpose of this study (1) to give an analytical survey of the Baptist Movement from 1612 to 1640 which serves as a background; (2) to show the development of Keach in his relation to the Baptist Movement from 1640 to 1689; (3) to present Keach as a pioneer and leader of the Baptist Movement from 1689 to 1704; and (4) to make a critical estimate of the work and thought of Benjamin Keach in the light of the Baptist Movement. Knowing the purpose, the next aspect is the method of procedure.
Keywords: Keach, Benjamin, 1640-1704; Baptist movement